Isolation and Molecular Characterization of Brotowali (Tinospora crispa) Rhizosphere Bacteria Producing Siderophore from Dry Lands of Lombok Island - Sekar Partiwi; Agil Al Idrus; Lalu Zulkifli; Mahrus; Prapti Sedijani (Jurnal Biologi Tropis, 2023)
In the context of biopesticide development, siderophore-producing rhizosphere bacteria play an important role as potential biological control agents. Siderophores are complex organic compounds produced by microorganisms to bind and take up iron ions (Fe3+) from the surrounding environment. This compound is very important because iron is a nutrient necessary for life for many microorganisms and plants. The aim of this research was to determine the type and ability of bacteria in the rhizosphere of Brotowali (Tinospora crispa) to produce siderophores. The method used in this research is an exploratory descriptive type. The isolation results obtained from the North Lombok area obtained 5 samples with codes B4A1, B6A1, BT61, BT63 and BT83. The results of the bacterial isolate potency test with Media Kings showed that only isolate BT63 showed clear fluorescence when exposed to ultraviolet light. Meanwhile, the Arnow's Assay test showed that only BT63 colonies experienced a color change to pink. The results of the molecular identification of the potential bacteria, namely BT63, using the BLAST method using the GenBank data base at NCBI, show that it is closely related to the species Bacillus thuringiensis strain FDAARGOS 791. The results above show that the rhizobacteria isolated from Brotowali have the potential to be developed as a natural biopesticide that can be applied in the future.